Elections in Asia and the Pacific / Vol. 1 The Middle East, Central Asia and South Asia (Elections in Asia and the Pacific, 2001)
This work continues the series of election data handbooks published by OUP. It presents a compendium of electoral data for all the 62 states in Asia, Australia and Oceania from their independence to the beginning of the 21st century.